(3Sei GdCfhGQ GdbhGejI aj GdCSQGQ GdcdGejIs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3eMeO Hf CHj HcQ Hf eMeO GdhQGb s)
(3ChdgG (B:s
(3GdMeO ddg GdeJYGdi HLdGd CMOjJg Yf eTGHgI GdCYQGV hGdLhGgQ CeG HYO adeG MGhdJ GdJbQH Edi eLdS adGf hgh GdPi NUg Gddg HGdfaS GdbOSjI s
(3BNQgG (B:s
(3Ke GNJdahG HYO ehJ GdMSf Ydi GKfi YTQ bhdkG (B: (3CMOgeG Cfg de jeJ dCfg dh eGJ hdjS dg hdO WGgQ dNdG GdReGf Yf GdEeGe GdeYUhe hPdc ZjQ LGFR hGddg CYde hCMce hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdfSNI ecedI HChQGb HNW eZGjQs
(3HChdgG bQGAI SfI (B695s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds